Ecofeminism in Indonesian fiction: Gender, land, and resistance in the era of environmental degradation - Ria Kasanova; Mohammad Rudiyanto; Sri Lestari; Lilis Sumaryanti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Ecocritical studies in Indonesian literature have developed rapidly; however, most still focus on the human–nature relationship without adequately integrating gender and postcolonial contexts into their analyses. This study aims to fill this gap by analysing the representations of the relationships between women, land, and power in Indonesian fiction through a postcolonial ecofeminist framework. The study focuses on three works: Tanah Tabu by Anindita S. Thayf, Saman by Ayu Utami, and Sihir Perempuan by Intan Paramaditha. This study used a qualitative approach with narrative and thematic analyses conducted through coding processes and comparative synthesis across texts. The results revealed three main patterns. First, women are represented as ecological victims in colonised and exploitative landscapes. Second, women appear as agents of resistance who negotiate power relations through their bodies and spirituality and through social practices. Third, women function as epistemic mediators who utilise local myths and spiritual knowledge to challenge the dominant ecological discourses. These findings show that literary works not only represent environmental crises but also produce alternative ecological knowledge that is grounded in local contexts. This study contributes to the development of ecofeminist studies by emphasising the importance of intersectional perspectives from Global South contexts in Indonesian literary studies and by expanding ecocriticism as a field of knowledge production and ecological resistance.